2018
DOI: 10.1017/ice.2018.75
|View full text |Cite
|
Sign up to set email alerts
|

Changing Epidemiology of Catheter-Related Bloodstream Infections in Cancer Patients

Abstract: We compared the etiologic organisms of bloodstream infections (BSIs) in cancer patients with central venous catheters (CVCs) between 2 cohorts separated by more than a decade.Gram-negative organisms have become the predominant etiologic organisms of BSIs (52%); they now contribute to 41% of catheter-related BSIs (CRBSIs).Infect Control Hosp Epidemiol 2018;39:727-729.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 10 publications
4
19
0
1
Order By: Relevance
“…This decreasing incidence has also been noted in other studies in general population patients [13][14][15], although to the best of our knowledge, this is one of the firsts studies showing these results in onco-hematological patients. Chaftari et al compared CRBSI in two different periods separated by over a decade [16]. Like our results, these authors showed a significant decrease in the rates of CRBSI between both periods, as well as an increase in the rates of GNB and proportional decrease in GPC.…”
Section: Plos Onesupporting
confidence: 85%
“…This decreasing incidence has also been noted in other studies in general population patients [13][14][15], although to the best of our knowledge, this is one of the firsts studies showing these results in onco-hematological patients. Chaftari et al compared CRBSI in two different periods separated by over a decade [16]. Like our results, these authors showed a significant decrease in the rates of CRBSI between both periods, as well as an increase in the rates of GNB and proportional decrease in GPC.…”
Section: Plos Onesupporting
confidence: 85%
“…E. coli and Klebsiella sp were the most common GN bacteria isolated in both groups. Our data are consistent with those from previous studies that evaluated the most common causative GN organisms in similar populations [1, 9, 13]. These findings are explained by the fact that MBI increases the risk of translocation of the gut microorganisms, such as E. coli and Klebsiella sp, to the systemic circulation.…”
Section: Discussionsupporting
confidence: 92%
“…Over the last 20 years, gram-negative (GN) organisms have become a major cause of bloodstream infections (BSIs), including central line-associated and catheter-related BSIs (CLABSIs and CRBSIs) and non-CLABSIs. This predominance mainly is seen in high-risk patients, such as cancer patients and intensive care unit patients [1–3]. Many studies have evaluated the common GN organisms seen in BSIs and their antimicrobial susceptibility patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os estudos atuais diferem entre si devido à epidemiologia local 46. Chaftari et al, em 2018, revisaram as ICS-CVC em pacientes oncológicos dos anos de 2013 e 2014 e perceberam uma grande mudança epidemiológica e etiológica dos últimos 20 anos em pacientes oncológicos, demonstrando uma equivalência entre ambas, porém predominando os BGN 90. A proporção de Enterobactérias foi significativamente maior entre os pacientes com neoplasias hematológicas.…”
unclassified